Chemical Composition of Longissimus dorsi and Biceps femoris on Different Slaughter Weight of Local Male Sheep Reared in the Village - Purbowati, E; Sutrisno, CI; Baliarti, E; Budhi, SPS; Lestariana, W (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
Quality of meat can be assessed from the change of its chemical components. Characteristics of meat chemical composition depend on species, age, sex, feed, location and function of muscle section in body. The objective of the research was to study meat chemical composition of local male sheep on different slaughter weight and different muscle. Local male sheep which were used as subject research obtained from Temanggung, i.e. healthy male sheep, aged 1.5-12 months; slaughtered at 6 categories of slaughter weight ranging from 5 to 30 kg. The sheep was slaughtered and sampled for chemical composition determination of Longissimus dorsi (LD) dan Biceps femoris (BF). The nested ANOVA was used to analyze data and any differences among the groups were further tested using Duncan Multiple Range Tests (DMRT). The results showed that moisture, ash, fat and cholesterol content of the meat from different slaughtered weight were not significant (P>0.05). The increase of slaughter weight significantly (P<0.05) increased the protein content of meat. Protein content of meat from 7, 10, 15, 20, 25 and 30 kg slaughtered weight were 18.44; 17.83; 18.70; 19.58; 19.44 and 20.06%, respectively. Vitamin A content from different slaughter weight were significant (P<0.05). Vitamin A content of meat from 7, 10, 15, 20, 25 and 30 kg slaughter weight were 682.06; 587.10; 612.59; 590.93; 663.32 and 590.84 µg/100 g meat, respectively. Moisture, ash, protein, fat, cholesterol and vitamin A from LD and BF muscle were not significant (P>0.05). The conclusion of the research were (1) moisture, ash, fat and cholesterol content of local male sheep meat from different slaughtered weight were not significant, but protein and vitamin A content of the meat from different slaughtered weight were significant, (2) chemical composition of local male sheep from LD and BF were not significant. (Animal Production 8(1): 1-7 (2006) Key Words : Male sheep, slaughter weight, longissimus dorsi, biceps femoris, chemical composition.